Peripheral nerves and plexus: imaging by MR-neurography and high-resolution ultrasound - Pham, Mirko; Bäumer, Tobias; Bendszus, Martin (Current opinion in neurology, 2014)
Purpose of review: The purpose of this study is to review advances in magnetic resonance (MR)-neurography and nerve-ultrasound for the precise visualization and localization of nerve lesions not only in nerve trauma or mass lesions, but also in entrapment-related and spontaneously occurring intrinsic neuropathies. These advances may improve the understanding and classification of peripheral neuropathies. Recent findings: Diagnostic studies of MR-neurography and high-resolution ultrasound in entrapment-neuropathies consistently report accurate determination and localization of symptomatic nerve entrapment. Additionally, the longitudinal sampling of nerve-T2-signal over larger areas of coverage has become technically feasible. With this approach, more complex patterns of spatial lesion dispersion in nonfocal neuropathies could be observed with reliable lesion image contrast at the level of individual nerve fascicles. Imaging detection of fascicular lesions allows for more accurate localization, because fascicular lesion types represent a specific pitfall for clinical-electrophysiological examinations. Fascicular hypoechogenicity of high-resolution ultrasound is the correlate of nerve-T2-signal lesions, but contrast is inferior and difficult to quantify. Therefore, nerve enlargement remains the main diagnostic criterion in high-resolution ultrasound. Diffusion-tensor-MR-neurography provides quantitative estimates of fiber structure, which were shown to correlate with aging and focal entrapment. Summary: High-resolution nerve imaging with extended anatomical coverage is feasible and improves the topographic description of spatial lesion dispersion which is particularly relevant for the discrimination between focal and nonfocal neuropathies.